Decoy state quantum key distribution - Ali, Sellami; Saharudin, Suhairi; Wahiddin, Mohamed Ridza (IIUM Press, 2009)
Experimental weak + vacuum protocol has been demonstrated using commercial QKD system based on a standard bi-directional ‘Plug & Play’ set-up. By making simple modifications to a commercial quantum key distribution system, decoy state QKD allows us to achieve much better performance than QKD system without decoy state in terms of key generation rate and distance. We demonstrate an unconditionally secure key rate of 6.2931 x 10-4 per pulse for a 25 km fiber length.